New genus and subgenus of South American long-horned bees (Apidae, Eucerini) - Freitas, Felipe V. (Zootaxa, 2022)
As part of a broader treatment of Eucerini systematics, a new genus and a new subgenus are described to accommodate previously described species. Savannychapis gen. n. is described to accommodate Gaesischia interrupta Urban 1989, originally described as a species of Gaesischia (Gaesischiana) Michener et al. 1955, and Gaesischia (Gaesischioides) subgen. n. to accommodate Gaesischia hyptidis (Ducke 1910), previously included in Gaesischia s. str. Michener et al. 1955 and G. (Agaesischia) Moure & Michener 1955. These new taxa are only known in the South American dry diagonal, a set of open vegetation biomes of central-eastern South America.